Light-Eye Interaction Physics Review - Owaid, Ahmed Y; Muhsen, Dhamiaa H (Journal of Asian Scientific Research, 2022)
As a result of advanced digital technology, we have become increasingly reliant on a global connectivity device such as laptops, tablets, and mobile phones. So, the interaction of human eyes with the industrial light of such devices becomes full of dangers caused by the short distance and the long duration of the view. With specific details, this study discusses and supports the physics of light-eye interaction. The physical treatment of light-eye interaction shows that the transmitted parts of the eye do not have a considerable amount of reflection, diffraction, scattering, or absorption of light rays, so they allow light to pass through them freely with some refraction. It has been established that about 98% of the incident light rays can pass through the eyes to reach the retina. The optical transmittance spectrum of the human eye has been shown to have a Gaussian shape with a center wavelength between 200 and 1400 nm. The duration of view, distance of vision, and shielding by a glassy substance have all been demonstrated to be effective procedures for protecting ourselves from the harmful effects of the screen light of handheld and tabletop digital devices. Moreover, it is reinforced that the prolonged viewing time on mobile devices is one of the most serious factors that leads to health problems in the eyes.